THE ESTABLISHMENT OF JAKARTA INTERNATIONAL SCHOOLIN INDONESIA AS A REFLECTION OF GLOBALISATION THROUGH EDUCATION - Rusdy, Brandon Cahyadhuha; Sunarti, Linda (International Review of Humanities Studies, 2025)
"This article examines the establishment of Jakarta International School (JIS) within the context of the globalisation of Indonesia. Established in 1951 under the name International School of Djakarta by Antoinette Stepanek, an educator from the United States, it was the first school to provide an English-language education for the children of expatriates in Jakarta, Indonesia. The school underwent several name changes throughout its history. In 1965, the school was renamed to Joint Embassy School to reflect the support from a coalition of embassies, consisting of the United States, United Kingdom, Australia and Yugoslavia. In 1978, the school was renamed again to Jakarta International School as it expanded and welcomed students from a broader international community. Finally, in 2014, it was again renamed to Jakarta Intercultural School aligning with Indonesian regulations restricting the use of the word “international” in school names. The establishment of JIS reflects globalisation and internationalism in Indonesia, particularly in the post-World War II and early post-independence context. JIS was founded to serve the children of expatriates such as diplomats, foreign businesspeople and development workers who had come to Indonesia following its internationally recognized independence in the late 1940s and early 1950s. The school itself is a symbol of international cooperation, and its establishment reflects Indonesia’s openness to international collaboration and the broader global trend of international schooling to support global mobility. From its modest beginnings in a house in Kebun Sirih to becoming the most recognized and renowned international education institution in the country with a sprawling academic complex that spans a total area of almost 19 hectares across its three campuses in South Jakarta, this paper provides an overview of the establishment of the school and how its growth mirrors broader global trends in international education and human mobility and is a reflection of globalisation in Indonesia. Utilising primary sources such as interviews with alumni and faculty members, and documents from archives, as well as secondary sources such as books and journal articles, this study aims to contribute to the historiography of education, diplomacy and globalisation in Indonesia. This paper will provide historical insights regarding the establishment of Jakarta International School and its connection to globalisation in Indonesia through the context of diplomacy and education. This research seeks to enrich the understanding of the intricate connections between international development, foreign policy and education."